Report on adverse events of COVID-19 vaccines in Iran: a comprehensive national prospective longitudinal analysis - Jamaati, Hamidreza; Karimi, Saeed; Arshi, Shahnam; Zahraei, Seyed Mohsen; Panahi, Yunes; Nouri, Fatemeh; Hajimoradi, Maryam; Hasanzade, Arman; Mokhtari, Majid; Tayeri, Katayoun; Abedini, Atefeh; Mohamadnia, Abdolreza; et al. (Frontiers in Immunology, 2025)
IntroductionThe global coronavirus disease 2019 (COVID-19) pandemic necessitated urgent vaccine development, raising concerns about potential vaccine adverse events (AEs).MethodsIn this prospective cohort study, conducted from February 2021 to December 2022, all individuals across Iran who received any COVID-19 vaccine dose and reported adverse events were investigated. Our aim was to evaluate these AEs based on the vaccine types, patients’ age and types of AES, and provide a comprehensive analysis.ResultsIn Iran, 155 million COVID-19 vaccine doses were administered, with Covilo (Sinopharm) being the most commonly vaccine administered (80.35%). Adverse events predominantly affected individuals aged 40-70 (45%). A total of 86,275 adverse events were recorded, with 92.7% classified as non-serious and 6 299 (7.3%) serious and among the serious cases, 279 were confirmed to be vaccine-related, with 46 resulting in fatalities and 233 requiring hospitalizations. The incidence of serious AEs was 0.41 per 10,000 doses. Serious AEs were more frequently associated with Sputnik V and Vaxzevria (AstraZeneca), with 0.73 and 0.64 cases per 10,000 injections, respectively. Coagulation and thrombosis disorders were the most common serious AEs (29%), followed by neurological (24.7%) and cardiovascular AEs (15.8%).DiscussionIn conclusion, the AEs of COVID-19 vaccination were primarily mild and transient, while serious AEs remained exceptionally rare.